2013
DOI: 10.1007/s12410-013-9198-0
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcium Testing in Symptomatic Patients: An Issue of Diagnostic Efficiency

Abstract: The detection and quantification of coronary artery calcification (CAC) significantly improves cardiovascular risk prediction in asymptomatic patients. Many have advocated for expanded CAC testing in symptomatic patients based on data demonstrating that the absence of quantifiable CAC in patients with possible angina makes obstructive coronary artery disease (CAD) and subsequent adverse events highly unlikely. However, the widespread use of CAC testing in symptomatic patients may be limited by the high backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…However, all those have significant limitations. Resting 12-lead ECG lacks adequate sensitivity and negative predictive, (12,13) and exercise ECG is a useful tool only in ambulatory patients for the detection of CAD. (14,15) Resting 2-D echocardiography (echo) has low sensitivity to predict cardiac events in patients with possible ACS (16) whereas, stress echo requires experienced technicians and readers with good image quality to maintain diagnostic accuracy and reproducibility (17).Single photon-emission CT (18) and perfusion imaging (19) are not ideal for initial evaluation and to rule out ACS for several reasons including cost, substantial exposure to radiation, time to perform a test and required a trained technician.…”
Section: Functional and Anatomical Cardiac Testing In Symptomatic Patientsmentioning
confidence: 99%
“…However, all those have significant limitations. Resting 12-lead ECG lacks adequate sensitivity and negative predictive, (12,13) and exercise ECG is a useful tool only in ambulatory patients for the detection of CAD. (14,15) Resting 2-D echocardiography (echo) has low sensitivity to predict cardiac events in patients with possible ACS (16) whereas, stress echo requires experienced technicians and readers with good image quality to maintain diagnostic accuracy and reproducibility (17).Single photon-emission CT (18) and perfusion imaging (19) are not ideal for initial evaluation and to rule out ACS for several reasons including cost, substantial exposure to radiation, time to perform a test and required a trained technician.…”
Section: Functional and Anatomical Cardiac Testing In Symptomatic Patientsmentioning
confidence: 99%
“…It has also been reported that the CAC score positively correlates with the number of coronary vessels affected by CAD, even in patients with proven CAD 35) , while an elevated CAC score is associated with higher morbidity and mortality rates 36) . Nevertheless, the general use of CAC scoring may be limited, as the high prevalence of CAC results in low specificity for obstructive CAD in symptomatic patients 37) . Furthermore, while the use of CAC scoring to guide decisionmaking regarding coronary CT is well established, the application of the CAC score for this purpose with respect to contrast-enhanced examinations has not been validated.…”
Section: Cac Score and Cardiovascular Morbidity And Mortality In The mentioning
confidence: 99%
“… 7 Among symptomatic patients, CAC generally has a high sensitivity and negative predictive value for excluding significant CAD and subsequent adverse cardiovascular events when performed in low-risk and intermediate-risk patients. 8 9 Although there are previous studies about associations between CAC and CAD, and the prognostic impact of CAC for cardiovascular outcomes, the sex-specific impact of CAC for CAD diagnosis is unclear. 9–11…”
Section: Introductionmentioning
confidence: 99%